WOOL PRODUCTIVITY OF LOCAL GOATS OF KARAKALPAKIA - А. U. Toreshova; R. Т. Aytjanov (American Journals Publishing, 2023)
The article presents the results of a study of haircuts and the quality of wool of local goats in Karakalpakstan.
Keywords: Clipping, wool length, length, gender, fiber types, age.